Bi-Layered Nanofibrous Mats For The Effective Treatment Of Infected Diabetic Wounds (International Journal of Environmental Sciences, 2025)
Diabetic foot ulcers (DFUs) remain one of the most severe complications of diabetes, often leading to chronic infections, prolonged hospitalization, and lower-limb amputations. Advanced wound dressings with multifunctional properties are essential to address both delayed tissue regeneration and infection control. In this study, a bi-layered electros pun nanofibrous mat was developed by combining two distinct functional layers: a PCL–Deferoxamine layer designed to promote angiogenesis and tissue regeneration, and a Chitosan–Collagen–PVA/Silver Sulfadiazine layer providing antibacterial protection and moisture balance. The mats were fabricated using optimized electrospinning parameters and characterized by SEM, FTIR, DSC, and XRD. SEM images revealed smooth, bead-free fibers with uniform morphology, while FTIR confirmed successful drug incorporation without significant chemical incompatibility. DSC and XRD results indicated a reduction in drug crystallinity, suggesting amorphous encapsulation, which is beneficial for solubility and sustained release. Collectively, the bilayer nanofibrous mats demonstrated favorable morphology, stability, and dual therapeutic potential, making them a promising candidate for the effective management of infected diabetic wounds.